Exploring the Interface Between Planetary Boundaries and Palaeoecology - Gillson, Lindsey; Seddon, Alistair; Mottl, Ondřej; Zhang, Ke; Kirsten, Kelly; Gell, Peter; Marchant, Rob A; Schwörer, Christoph; Razanatsoa, Estelle; Lane, Paul J; Courtney-Mustaphi, Colin J; Dearing, John (Global change biology, 2025)
The concepts of planetary boundaries are influential in the sustainability literature and assist in delineating the 'safe operating spaces' beyond which critical Earth system processes could collapse. Moving away from our current trajectory towards 'hothouse Earth' will require knowledge of how Earth systems have varied throughout the Holocene, and whether and how far we have deviated from past ranges of variability. Such information can inform decisions about where change could be resisted, accepted or where adaptation is inevitable. The need for information on long-term (Holocene) change provides an interface for palaeoecology and sustainability that remains underexploited. In this position paper, we explore this interface, first discussing the need for long-term perspectives and introducing examples where palaeoecology has been used in defining safe operating spaces and constraining limits of acceptable change. We describe advances in quantitative methods for analysis of time-series data that strengthen the contribution of palaeoecology to the concepts of planetary boundaries and safe operating spaces. We consider the importance of issues of scaling from landscape to regional and global scales in operationalising planetary boundaries concepts. We distil principles for this field of research going forward and introduce three case studies which will form the basis of research on these topics.
Keywords: variability; Earth, Planet; safe operating space; klimatické změny; Paleontology; planetary boundaries; ekologie; Ecology; resilience; Climate Change; paleontologie; sustainability; tipping points; Země (planeta); palaeoecology